Theoretical perspectives on the socio-environmental conflict over oil exploration - Rojas-Bahamón , Magda Julissa; Arbeláez-Campillo , Diego Felipe (Seven Editora, 2024)
The paper analyzes the socio-environmental conflicts related to oil exploration from various theoretical perspectives. Post-materialism, political ecology, ecological economics, environmental justice, and decolonial theories are examined. Each approach brings a unique insight: post-materialism explains environmental concern in developed societies, while political ecology focuses on the underlying power relations. Ecological economics emphasizes biophysical limits and criticizes unlimited economic growth. Environmental justice highlights inequity in the distribution of environmental risks and benefits. Decolonial theories address how colonial legacies influence the exploitation of resources and the marginalization of communities. The paper illustrates these concepts with case studies from Colombia, Ecuador, Argentina, and other countries, demonstrating how local communities resist extractive projects that threaten their territories and ways of life. It is concluded that socio-environmental conflicts are complex, rooted in historical dynamics and structural inequalities, requiring a comprehensive approach for their understanding and resolution. DOI:https://doi.org/10.56238/sevened2024.026-049